The Effect of Solid Organic Fertilizer Application on the Growth of Bede Grass (Brachiaria decumbens) - Emanuel Sedan; Nyoman Pande Aryanti; Ni Ketut Etty Suwitari; I Gusti Ayu Dewi Seri Rejeki (Agriwar Journal, 2026)
Bede grass (Brachiaria decumbens) is a high-quality forage plant commonly used as green fodder due to its favorable growth characteristics, biomass production, and nutritional value. This study aimed to evaluate the effect of solid organic fertilizer application and different fertilizer doses on the growth and production of Bede grass. The experiment was conducted using a randomized block design with five treatments and three replications. The treatments consisted of P0 (without solid organic fertilizer), P1 (10 tons/ha), P2 (20 tons/ha), P3 (30 tons/ha), and P4 (40 tons/ha) of solid organic fertilizer. The results showed that the application of solid organic fertilizer had no significant effect (P>0.05) on most growth and production parameters of Brachiaria decumbens, except for fresh leaf yield, which was significantly affected (P<0.05). These findings indicate that the application of solid organic fertilizer at different doses did not significantly influence vegetative growth. However, the application rate of 30 tons/ha tended to produce better growth and yield compared to other treatments, although the differences were not statistically significant. Further research is recommended to consider environmental factors such as soil properties and light intensity to better understand the response of Brachiaria decumbens to solid organic fertilizer. The use of a 30 tons/ha fertilizer dose may be considered due to its tendency to provide optimal results.